2022
DOI: 10.1001/jamanetworkopen.2021.48325
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Racial, Ethnic, and Geographic Location Diversity of Participants Enrolled in Clinic-Based vs 2 Remote COVID-19 Clinical Trials

Abstract: IMPORTANCERacial and ethnic diversity among study participants is associated with improved generalizability of clinical trial results and may address inequities in evidence that informs public health strategies. Novel strategies are needed for equitable access and recruitment of diverse clinical trial populations. OBJECTIVE To investigate demographic and geographical location data for participants in 2 remote COVID-19 clinical trials with online recruitment and compare with those of a contemporaneous clinic-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Several descriptive studies have also highlighted the importance of partnering with diverse community stakeholders in the recruitment process to engage minority populations in research [10]. A more recent study compared demographics of participants enrolled in COVID-19 clinical trials by in-person recruitment versus those enrolled by online recruitment, including social media advertising; online advertising with inclusive social media recruitment led to increase in racial, ethnic, and geographic diversity among study participants [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several descriptive studies have also highlighted the importance of partnering with diverse community stakeholders in the recruitment process to engage minority populations in research [10]. A more recent study compared demographics of participants enrolled in COVID-19 clinical trials by in-person recruitment versus those enrolled by online recruitment, including social media advertising; online advertising with inclusive social media recruitment led to increase in racial, ethnic, and geographic diversity among study participants [11].…”
Section: Discussionmentioning
confidence: 99%
“…This includes access to internet, the different virtual platforms and information on research opportunities. A recent study covid-19 trial reported on the power of social media and digital technology to increase participation of diverse populations in clinical trials 12 . There is a critical positive opportunity here to leverage for future trials where more patient centered trials can increase participation by diverse communities because of the ability to have visits while at home, at work, on nonwork hours and without the added expense, time and stress to travel to a center.…”
Section: Covid-19 and Clinical Trialsmentioning
confidence: 99%
“…On the international familial hypercholesterolemia (FH) awareness day, dedicated to a chronically underdiagnosed but life-threatening disease, a significant increase in FH-related twitter metrics was observed [ 55 ]. Finally, such outreach programs can be used for patient recruitment to clinical trials [ 56 ] outside of the classical hospital-centered clinical research atmosphere in so-called remote clinical trials fostered by the COVID-19 pandemic [ 57 ].…”
Section: Social Media In Medicinementioning
confidence: 99%